2020
DOI: 10.21292/2075-1230-2020-98-8-24-31
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence in lung cancer screening: assessment of the diagnostic accuracy of the algorithm analyzing low-dose computed tomography

Abstract: The diagnostic accuracy of the artificial intelligence algorithm aimed to detect lesions on low-dose computer tomograms has been independently assessed. The dataset formed as part of the lung cancer screening program in Moscow was used. The following indicators have been defined: sensitivity – 0.817%, specificity – 0.925%, accuracy – 0.860%, area under the characteristic curve – 0.930. High accuracy rates demonstrated through the independent assessment indicate a good reproducibility of the results by artifici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
(2 reference statements)
0
1
0
1
Order By: Relevance
“…Philips Research Lung Cancer Screening (LDCT LC) service demonstrated comparable performance with an initial AUC of 0.930, and at the retrospective stage of the Experiment – 0.92. In the prospective study, AUC decreased to 0.78, followed by specificity (prior – 0.925, retrospectively – 0.87, prospectively – 0.68) 23 . We also previously tested the FBM (FLG) service on two datasets with a balance of normal-to-pathology 50/50 and 95/5 with resulting AUC of 0.74 and 0.64, sensitivity – 0.872 and 0.75, specificity – 0.60 and 0.535, concluding that the accuracy varied depending on the class balance 24 .…”
Section: Discussionmentioning
confidence: 84%
“…Philips Research Lung Cancer Screening (LDCT LC) service demonstrated comparable performance with an initial AUC of 0.930, and at the retrospective stage of the Experiment – 0.92. In the prospective study, AUC decreased to 0.78, followed by specificity (prior – 0.925, retrospectively – 0.87, prospectively – 0.68) 23 . We also previously tested the FBM (FLG) service on two datasets with a balance of normal-to-pathology 50/50 and 95/5 with resulting AUC of 0.74 and 0.64, sensitivity – 0.872 and 0.75, specificity – 0.60 and 0.535, concluding that the accuracy varied depending on the class balance 24 .…”
Section: Discussionmentioning
confidence: 84%
“…Для обеспечения системности организации медицинской помощи больным ключевое значение имеет цифровизация здравоохранения [13,14], позволяющая осуществить сбор, обработку и накопление достоверных статистических данных, оптимизацию маршрутизации пациентов, а также содержит систему поддержки врачебных решений [15][16][17]. Процессный подход в оказании медицинской помощи обычно рассматривается с позиции организации процессов на уровне МО [18,19].…”
Section: Introductionunclassified